Epidemic of Sal Heart-wood BorerHoplocerambyx spinicornis Newm. (Coleoptera : Cerambycidae) and its Control in Pachmari, Madhya Pradesh - Bhandari, R. S.; Singh, Pratap (Indian Forester, 1988)
Epidemic of Sal heart-wood borer, Hoplocerambyx spinicornis, was reported in 1979 from the hill resort of Pachmari, Madhya Pradesh. The very existance of Sal around Pachmari was threatened. Sal forest has great aesthetic value for this hill resort. So extensive trapping operations were carried out from 1979 to 1981 to control the borer, which brought down the incidence of attack from 57.23 per cent in 1979 to 0.75 per cent in 1981 and mortality from 12.28 per cent to 0.0 per cent which are below the tolerance levels.